Nigeria 2011 : An Assessment of the Investment Climate in 26 States - Iarossi, Giuseppe (World Bank, Washington, DC, 2017)
This investment climate analysis reviews the experiences of over 3000 surveyed business owners in 26 states of Nigeria about the aspects of the business climate that affect their businesses. It complements a similar study in 2007 that covered 11 other Nigerian states. The survey asks business owners about both their perceptions and the actual costs of selected constraints. The analysis benchmarks Nigeria against comparator countries, and provides detailed data for each state. Nigerian firms have low productivity, as measured by their output in relation to their labor and capital inputs. Firms in Kenya are about 40 percent more efficient, firms in Russia almost twice as productive, and firms in South Africa almost four times as productive. Nigerian firms that export are about 90 percent more productive than non-exporters. Although labor in Nigeria is inexpensive, it is not inexpensive enough to compensate for this low productivity. The poor performance of Nigerian firms reflects many factors. This study focuses on constraints in the business climate and the serious costs they impose on Nigerian firms. Taken together, the total indirect costs of poor quality infrastructure, crime and security, and corruption amount to over 10 percent of sales for Nigerian firms. This is twice as high as in South Africa, Brazil, Russia and Indonesia. Microenterprises firms with fewer than five workers face similar constraints as larger firm's unreliable power, limited access to finance, corruption, and transportation bottlenecks. But the consequences for their businesses are far more severe. For instance, most microenterprises cannot afford generators, so power outages are more likely to shut down their operation. Lacking collateral, almost no microenterprises have access to formal external financing.